2020
DOI: 10.1177/1120700020972025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time to surgery in neck of femur fracture patients with ASA Grade of 3 and above

Abstract: Introduction: Hip fractures are an important cause of morbidity and mortality. Early surgery has been shown to reduce mortality rates and surgical complications. The American Society of Anesthesiologists (ASA) grade is a widely used tool to assess preoperative health of patients. This study aims to assess is whether delay in surgical time has a greater impact on the mortality rates for high risk patients. Method: Retrospective study using the National Hip Fracture Database (NHFD) of 4883 neck of femur fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…Dar et al suggested that having delayed surgery did not significantly increase mortality [ 19 ]. The findings of this study are quite contradictory to a systematic review done by Khan et al, who suggested early surgery for hip fractures decreases both the mortality and length of hospital stay [ 20 ]. In our study, 70% of patients who had delayed surgery of more than 36 hours died within 120 days of surgery (p < 0.001).…”
Section: Discussioncontrasting
confidence: 99%
“…Dar et al suggested that having delayed surgery did not significantly increase mortality [ 19 ]. The findings of this study are quite contradictory to a systematic review done by Khan et al, who suggested early surgery for hip fractures decreases both the mortality and length of hospital stay [ 20 ]. In our study, 70% of patients who had delayed surgery of more than 36 hours died within 120 days of surgery (p < 0.001).…”
Section: Discussioncontrasting
confidence: 99%
“…After controlling for all these factors simultaneously, the multivariable logistic regression revealed the only factor independently associated with 90-day mortality was a night operation. This is an interesting finding considering that most studies identifying time from admission to OR as a significant factor for mortality did not control for operative start time (day versus night) in their analyses [6,12,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, traditional thinking regarding admission to OR time has also been reassessed in the setting of delaying procedures due to patients' anticoagulation medication [26]. It is also believed that comorbid status may mediate the relationship between time to surgery and mortality [16,27]. Furthermore, other esoteric factors such as those involving the resources of the patient's health care system and surgeon variability may also influence this relationship but are not fully captured by current research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A delay in femoral fracture consultations of more than 5 days may raise important questions about the health care system and the impact of this delay on patients such as the influence of prognosis and increased risk of complications (32). Surgical delay beyond 36 hours for surgery has a greater impact on mortality for patients with higher preoperative health grades (33).…”
Section: Discussionmentioning
confidence: 99%